Islamic Family–Based Group Guidance and Counseling in Students’ Academic Decision-Making - Maslina Daulay; Darwin Harahap (Bulletin of Counseling and Psychotherapy, 2026)
These difficulties are further exacerbated by the suboptimal implementation of group guidance and counseling services, particularly in facilitating academic decision-making processes that incorporate Islamic family values as moral and spiritual foundations. This study aims to analyze strategies for enhancing group counseling services based on Islamic family values in assisting students with academic decision-making related to the selection of university study programs. The research employed a descriptive qualitative approach using interviews, observations, documentation, and Focus Group Discussions (FGDs) involving school principals, guidance and counseling counselors, and experts in Islamic guidance and counseling. Data were analyzed using the Miles and Huberman interactive model. The findings indicate that the integration of Islamic family values such as shura (consultation), amanah (trustworthiness), ta’awun (mutual assistance), and maslahah (public benefit) strengthens students’ self-reflection, enhances their confidence in making independent decisions, and improves academic communication between students and parents. This study recommends the development of an Islamic family values–based group counseling model and the implementation of career planning program.